DETERMINAN IMPOR GARAM KE INDONESIA - Wesly Noviandre; Made Heny Urmila Dewi (Universitas Udayana, 2024)
The purpose of this study is to describe the development of production, exchange rate consumption, GDP, and salt imports in Indonesia, as well as analyze the simultaneous or partial influence of salt production, salt consumption, Rupiah exchange rate, and GDP on Indonesia's salt import demand. This study used a quantitative approach in the form of associative research. This research took place in Indonesia. The data collection method used in this study was non-behavioral observation. The data analysis used in the study was a regression panel of data that was analyzed using the SPSS 26.0 program. The results of this analysis show that salt production, salt consumption, exchange rates, and GDP simultaneously have a significant effect on Indonesia's salt imports. Salt production and exchange rates partially have a negative and significant effect on Indonesia's salt imports, while salt consumption and GDP have a positive and significant effect on Indonesia's salt imports.Keywords : salt production, salt consumption, Rupiah exchange rate, GDP, imports